Mitigasi Bencana Berbasis Kearifan Lokal di Kecamatan Kejajar Kabupaten Wonosobo - Ninik Tri Kusumadewi; Suwarno Suwarno (Proceedings Series on Social Sciences & Humanities, 2022)
Wonosobo district is a mountainous area that is prone to natural disasters. Entering the rainy season, all people are asked to be vigilant and alert to the threat of landslides. Disasters are a common thing experienced by the community and become a problem in it self. Facing a disaster there is no need to panic but be alert, build disaster mitigation and carry out socialization. People who are used to dealing with disasters will have local wisdom in disaster mitigation. Local wisdom is the experience of events that have occurred in the area. This research was conducted in Kejajar District, Wonosobo Regency. Kejajar sub-district is one of the sub-districts in Wonosobo district which is prone to landslides and there have been flash floods that submerged dozens of houses. The method used in this research is descriptive qualitative with a functional structural approach related to the community. The purpose of this study is to analize disaster mitigation efforts based on local wisdom by the people of Kejajar sub-district. The result of this research community has a common awareness to carry out disaster mitigation, namely by their habit of going out of the house to a place that feels safer and carrying goods/securities when it rains continuously with a high intensity of more than 2 hours. Periodically a maximum of once a month, the community carries out mutual cooperation activities or community service to clean ditches, rivers and carry out reforestation and do not forget to hold socialization about floods, landslides and no less important is the understanding that the community has that they aremust be wise to nature.